Pengidentifikasian Nilai-nilai Kearifan Lokal dalam Menghindari Intoleransi di Kabupaten Kubu Raya Provinsi Kalimantan Barat - Martinus Martinus; Andreas Muhrotien; Gustaf Hariyanto; Amadi Amadi; Carolina Lala; Felisitas Yuswanto (UIN Sunan Kalijaga Yogyakarta, 2021)
Some studies indicate that a cultural approach is often referred to explain conflict. Culture is the factor that makes a group of people come together, have the same understanding of who they are. This study aims to promote identity and difference with the use of cultural symbols considered an effective way to strengthen a sense of togetherness, and to act collectively in achieving certain goals. The paper is based on original research that emploes qualitative-descriptive approach. Data was collected through observation, in-depth interviews and literature studies based on relevant sources. This work suggests that local wisdom of each ethnicities was able to become the key elements of ethnic group understanding and peacebuilding which was preserved in organizational forms, art studios, culture and brought together to carry out Cultural Titles. The cultural dimension remains important because not all law enforcement, justice and human rights mechanisms in conflict areas have been successful in creating lasting peace between the conflicting parties. Therefore, the use of a cultural perspective in integrating cultural factors in conflict resolution and peacebuilding mechanisms should always be considered.